Optimization of Conventional Solid-Liquid Extraction and Microwave-Assisted Extraction of Polyphenols and Antioxidant Compounds of Blueberry (Vaccinium Corymbosum) Pomace Through Response Surface Methodology - Bustos-Cerda, R; Florez-Mendez, J (IOS Press BV, 2021)
BACKGROUND: Blueberries contain large amounts of phenolic compounds as well as a higher concentration of anthocyanins than other berries. The peel of these fruits contains most of the anthocyanins and therefore pomace is left with the largest quantity of valuable phenolic compounds. Extraction is the most critical step to obtain such compounds. OBJECTIVE: This study aims to optimize the extraction of polyphenols and antioxidant compounds from blueberry pomace by solid-liquid extraction (SLE) and microwave-assisted extraction (MAE). METHODS: A Pareto chart was used to confirm the factor with the highest impact, response surface for analyzing the effect of extraction conditions on total phenol content (TPC) (through Folin-Ciocalteu), total anthocyanin content (TAC) (through differential pH), antioxidant capacity (AC) (through DPPH assay) and the Box-Behnken matrix to determine the optimal conditions for marc extraction with each method. RESULTS: Ethanol concentration is an impact factor for both methods, as well as irradiation method, radiation power for MAE and temperature for SLE. Regarding SLE and MAE extraction, under optimal conditions, a TCP content of 335.95 and 426.19 (mg GAE/100 g), TAC 272.69 and 389.64 (mg Cyn-3-glu/100 g), and CA 528.96 and 654.11 (mg TE/100 g) was obtained, respectively. CONCLUSIONS: The performance of phenolic compound extraction via MAE method is better than that of SLE. © 2021 - IOS Press. All rights reserved.